The care of dying people in 16th- and 17th-century England. Issue 5 (3rd May 2020) - Germain, Lewis; Sabroe, Ian
Abstract: Between the years 1500 and 1700, mortality was higher and exposure to death is greater than in the modern day. Through analysis of primary texts from the chosen period, we explored the principles behind the care of the dying in the context of medicine, spirituality, and society. Results showed that a "holy death" was a cultural norm and medicine was subsidiary: hope was for the salvation of the soul, not the body. This was part of an approach that focused on symptom relief, irrespective of disease classification, demonstrating an early holistic approach to death and dying.